1996
DOI: 10.1597/1545-1569_1996_033_0127_cothho_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hearing Histories of Children with and without Cleft Palate

Abstract: Aggressive otologic management has been recommended for children with cleft palate because of the almost universal occurrence of otitis media with effusion (OME) in these children and the association of OME with hearing loss and possible language, cognitive, and academic delays. In this study, 28 children with cleft palate and 29 noncleft children were seen at 3-month intervals from 9 to 30 months to compare otologic treatment and management. Hearing and middle ear function were tested at each session; informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 17 publications
6
32
1
2
Order By: Relevance
“…Mild and moderate conductive fluctuating hearing loss is well described to be one of the major problems in cleft palate population [14,15]. It has been suggested that because our cleft palate patients after 1-stage palatoplasty suffered, at a great percentage (69%), from mild to moderate hearing loss, their early persistent seromucous otitis may be responsible not only for the later otologic abnormalities and hearing impairment but also for their reportedly prevalent impairment at speech and language.…”
Section: Discussionmentioning
confidence: 99%
“…Mild and moderate conductive fluctuating hearing loss is well described to be one of the major problems in cleft palate population [14,15]. It has been suggested that because our cleft palate patients after 1-stage palatoplasty suffered, at a great percentage (69%), from mild to moderate hearing loss, their early persistent seromucous otitis may be responsible not only for the later otologic abnormalities and hearing impairment but also for their reportedly prevalent impairment at speech and language.…”
Section: Discussionmentioning
confidence: 99%
“…OME is associated with a mild to moderate conductive hearing loss with levels fluctuating between 0 and 55 dB across the speech frequencies [14]. In the four previously cited studies, all have reported hearing sensitivity, with only two relating it to OME [12,24]. The two studies had opposing findings.…”
mentioning
confidence: 99%
“…The two studies had opposing findings. Valtonen et al [24] found ears with OME demonstrated a low percent of hearing loss (PTA > 15 dB); while Broen et al [12] found children with clefts and who had failed tympanometry demonstrated poorer hearing thresholds than children who passed tympanometry.…”
mentioning
confidence: 99%
See 2 more Smart Citations